Phytochemical Components and Antimicrobial Efficacy of Rosemary Plant (Rosmarinus Officinalis) Extract - Mousawi, Heyam G. Al (American Journal of Biology and Natural Sciences, 2024)
Rosemary is a well-known restorative plant for its aromatic characteristics. The confirmed diagnosis of R. officinali was made in the laboratory of the Faculty of Pharmacy/University of Babylon. Numerous extracts and chemical compounds were achieved as well the antimicrobial impacts of R. officinali were exanimated against 3 bacterial strains: Escherishia coli (E. coli), Pseudomonas aeruginosa (P. aeruginosa) Staphylococcus aureus (S. aureus), and one type of fungi: Candida albicans (C. albicans) applying agar well diffusion method and con. ranging from 500 to 3000 mg/mL. The outcomes of the chemically analysis of R. officinali leaves extracts demonstrated that the aqueous extract contained phenols, Flavonoids, Terpeniods, while be lacking Resins, Tanins and glycosids. The Alcohol one contained phenols, Flavonoids, Terpeniods, and Resins, while be lacking Tanins and glycosids. All exanimated isolates showed sensitivity to both extracts of R. officinali at a con. of 3000 mg/ml, where this con. of both extracts displayed increased inhibition zone diameters in S. aureus, C. albicans and E. coli respectively, as compared with P. aeruginosa. The ultimate effectual inhibition for R. officinali aqueous extract was recorded against E. coli, while the least inhibition zone had found in P. aeruginosa. As regards R. officinali alcoholic extracts, the maximum inhibition zone had found in S. aureus, while the least impact was observed on P. aeruginosa. Conclusion: Current results imply that rosemary extracts may be used as naturally antibacterial and antifungal agent in medicinal setting.